Seeding times of triticale in Capão Bonito, SP - Felicio, João Carlos; Camargo, Carlos Eduardo Oliveira; Castro, Jairo Lopes de; Camargo, Marcelo Bento Paes de (Pesquisa Agropecuaria Brasileira, 1999)
Ten triticale and two wheat genotypes were evaluated at three seeding times (21st to 31st of March, 11th to 20th of April and 21st to 31st of May) for grain yield, test weight and 1,000 grain weight in experiments carried out at Capão Bonito Experiment Station (SP, Brazil), in the period 1991-95. Soil water availability was obtained by water balances taken at ten days intervals considering 100 mm as the soil retention capacity. The results indicated that the first seeding time was the best for the evaluated parameters. In relation to grain yield genotypes IAC 2 and BGL"S"/CIN"S"//MUS"S" presented good performance at the three seeding times. The genotypes IAC 3, Hare 212, Ardilla"S" and ICT 8803 showed high production at 2nd and 3rd seeding times and the genotype MERINOS"S"/JLO"S"/3/BGL"S"/CIN"S"//MUS"S" only at the 3rd seeding time. The best genotype was IAC 2, independent of the seeding time. Grain yield was associated with 1,000 grain weight. The occurrence of the causal agents of leaf spots was more intense in leaves of the wheat genotype IAC 24 than in triticales except for CEP 15.